IMPORTANCE OF THE SILK ROAD AND THE SILK ROAD ECONOMIC BELT PROJECT - Baltabayeva А. Yu.; Abubakirova A.T.; Syzdykova А.О. (Scientific Journal of Pedagogy and Economics, 2021)
The interaction of different political, economic, historical and cultural dynamics of societies play an important role in the emergence of civilizations. The interaction of these dynamics with each other was realized by means of transportation due to reasons such as trade, migration, war, diplomacy. Transportation routes have been the most important element that provides the relationship of space between people and societies through the means that have developed in the historical process. The factor that makes the transportation route valuable and lasting depends on its geopolitical and geostrategic position, on ensuring that the societies carry out their social and economic relations safely. In this context, the oldest and most valuable transportation route in human history is the Silk Road, which covers a large geography from Europe to Asia to Asia to Africa, where many ancient civilizations were born. Along with the increase in the importance of energy resources in recent years, the importance of the Silk Road has increased as a result of the growing role of the countries concentrated in the region along the Silk Road in the world economy. On September 7, 2013, Chinese President XI Jinping delivered an important speech at Nazarbayev University in Astana, calling on China and Central Asia to join the creation of a new "silk road Economic belt". According to some researchers, this project covers the European economic zone from China and the Eurasia and Asia-Pacific economy corridor. China's project to revive the Silk Road has emerged as a result of China's economic and political-based regional and global expectations and concerns, rather than being a utopian initiative. In this study, new projects in the revitalization of the Silk Road were evaluated and the Silk Road Economic Belt project was studied. The environmental threats posed to the region by the world's largest transport project, which is being implemented with the participation of 65 countries, were discussed.